Multicenter study on prognostic influencing factors of endovascular treatment for acute basilar artery occlusion - HAO Peng; TAO Chun⁃rong; JING Xiao⁃zhong; LI Rui; LUO Cong; HU Wei (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To screen the prognostic influencing factors of patients with endovascular treatment for acute basilar artery occlusion (ABAO⁃EVT). Methods The baseline, clinical and follow⁃up data of 215 patients with ABAO⁃EVT from October 2017 to August 2022 in The First Affiliated Hospital of University of Science and Technology of China, Linyi People's Hospital of Shandong and Maoming People's Hospital of Guangdong were retrospectively collected, including sex, age, stroke or transient ischemic attack (TIA), hypertension, diabetes, coronary heart disease, atrial fibrillation, smoking and drinking history, National Institutes of Health Stroke Scale (NIHSS) score, intravenous thrombolysis, first pass effect, times of embolectomy, extended Thrombolysis in Cerebral Infarction (eTICI), and modified Rankin Scale (mRS) score 90 d after operation. According to the 90 d mRS score, the patients were divided into 2 groups: good prognosis group (mRS score 0-3, n = 93) and poor prognosis group (mRS score 4-6, n = 122). Univariate and multivariate stepwise Logistic regression analyses were used to screen the neurological prognostic influencing factors of ABAO ⁃ EVT patients 90 d after operation. Results Logistic regression analysis showed that the baseline NIHSS score increased was a risk factor for poor prognosis of ABAO⁃EVT patients (aOR = 0.936, 95%CI: 0.907-0.965, P = 0.000; aOR = 0.940, 95%CI: 0.910-0.970, P = 0.000), with the first pass effect (aOR = 5.752, 95%CI: 2.875-11.508; P = 0.000), eTICI grade 2c-3 (aOR = 7.113, 95%CI: 3.665-13.805; P = 0.000) were protective factors for good prognosis. Conclusions Low baseline NIHSS score, first pass effect and reperfusion level of eTICI 2c-3 are all protective factors for good neurological prognosis of ABAO⁃EVT patients.